(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article examines the current significance of information technologies and artificial intelligence in the processes of drug production, as well as ways of their practical application. IT and II technologies are being introduced into the pharmaceutical industry, and the production of new medicines is being established. At the same time, artificial intelligence plays an important role in determining the molecular structure of new active substances through the analysis of biological and chemical data, optimizing clinical trials, and developing personalized medicines. Also, IoT, Big Data, and blockchain technologies are used to increase production efficiency and ensure the authenticity of medicines in the supply chain. Thus, modern IT and artificial intelligence technologies are one of the key factors in the digitalization and innovative development of the pharmaceutical industry.